The EU Services Directive: Untapped potentials of trade in services - Yvonne Wolfmayr; Michael Pfaffermayr (FIW - Research Centre International Economics, 2022)
The biggest reform step to date in the liberalisation and deepening of the EU internal market for services was taken with the EU Services Directive. Its implementation intended to provide a clear impetus for the removal of existing obstacles to the free movement of services, the freedom of establishment of services providers and for administrative simplification. The project quantifies the Directive's effects on Austrian and EU services trade and welfare but also highlights untapped potentials due to remaining administrative barriers and existing weaknesses in the implementation and enforcement of the Single Market rules. The estimation relies on a structural gravity model estimated on a disaggregated industry level.
Keywords: 330